Avaliação microestrutural da liga de alumínio AA7050 com diferentes multiestágios de envelhecimento - Renaudin, Luiz Baliski (2019)
Aluminium is one of the most used materials in the aeronautic industry because of its properties, as low density, corrosion resistance, and high strength. Some of these qualities are achieved just after some heat treatment. The AA7050 aluminium alloy is mostly used on the structure of the aircrafts because it has one of the highest strength between the aluminium alloys after some ageing treatment. During these heat treatments the AA7050 form precipitates between and within its grains, those tiny structures give the desirable additional strength to the alloy. In this work, there were tested five different multistage ageing heat treatments, they are the RRA (Retrogression and Re-Ageing), T6I4-65 (interrupted ageing), T7451 (most used on industries), RRA 2%, and T6I4-65 2% (cold rolling with reduction of 2% in the thickness, done between the temper and the first ageing). All the five studied ageing treatments are with multistage, which means, there are more than one ageing step in the heat treatment as a whole. Improving not only strength, but also other desirable properties, as ductility and corrosion resistance. With the micro Vickers hardness results, was possible to identify the relationship of microhardness and the different stages of the ageing treatments. With optical microscopy was identified the morphology of the grains, and to analyze the precipitates was used the TEM (Transmission Electron Microscopy) and DSC (Differential Scanning Calorimetry) analyses. Was identified that on the first ageing at 130 °C, is the main responsible for the formation and growth of GP zones (GPI and GPII) and the η’ phase for the RRA and T6I4-65 (with and without cold rolling) ageing treatments. The reversion step of RRA was capable of dissolving some GP zones. The RRA condition presented a subtle higher microhardness than the T6I4-65, even with similar quantities of GP zones and the main responsible precipitate for hardening, the η’phase. The higher microhardness is probably an effect of a higher number of smaller precipitates in the RRA condition. The cold rolling with reduction of 2% in the thickness, did not show up any significant difference to the samples without this step. All the four multistage ageing treatments carried out in this work presented higher microhardness than the commercial T7451.